2023
DOI: 10.1080/07853890.2023.2175031
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical determinants of length of stay, readmission and recurrence in patients admitted with diabetic ketoacidosis

Abstract: Background The increasing prevalence of diabetic ketoacidosis (DKA) related admissions poses a significant burden on the healthcare systems globally. However, data regarding the predictors of healthcare resource utilization in DKA is limited and inconsistent. This study aimed to identify key predictors of hospital length of stay (LOS), readmission and recurrent DKA episodes. Methods We undertook a retrospective cross-sectional analysis of all DKA admissions from 2015 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…To our knowledge, this is the first risk prediction model for prolonged ICU LOS in patients with DKA. This distinguishes our study from previous research [ 7 , 10 ] that primarily focused on identifying factors influencing LOS in patients with DKA. In this study we simultaneously screened multiple variables using LASSO, enhancing the precision of the final inclusion in the nomogram.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…To our knowledge, this is the first risk prediction model for prolonged ICU LOS in patients with DKA. This distinguishes our study from previous research [ 7 , 10 ] that primarily focused on identifying factors influencing LOS in patients with DKA. In this study we simultaneously screened multiple variables using LASSO, enhancing the precision of the final inclusion in the nomogram.…”
Section: Discussionmentioning
confidence: 95%
“…The length of hospitalisation in patients with DKA may be influenced by their prognosis. Ata et al [ 7 ] showed that patients with DKA with longer hospitalisation periods are at a higher risk of comorbidities, leading to a poor prognosis, further increasing the economic burden, and creating a vicious circle. Patients with DKA treated in general wards have been reported to exhibit no significant difference in mortality rate but had lower treatment costs compared to patients with DKA admitted to the ICU [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 It may also indicate how poorly controlled diabetes over the preceding months of acute presentation affects the general health of diabetic patients which leads to a more protracted stay in hospital. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Ata et al examined the differences in the number of DKA episodes during Ramadan compared to the rest of the year in patients with T1D and T2D in Qatar with view to examine the seasonality of DKA between 2015 and 2021. 41 Of 922 patients, 52% had T1D and 48% had T2D. The median age was 35 years.…”
Section: Highlights Of the Literaturementioning
confidence: 99%